The Use Of Couple Marriage Counseling Techniques - Anisha Putri Setiawan (PT. Anagata Sembagi Education, 2024)
Problems in marital relationships often lead to disharmony in the household, which in turn can negatively affect family members, especially children. Therefore, marriage counseling services by a professional such as a counselor are important. The Couple Marriage Counseling technique aims to prevent and overcome problems in marital relationships. The qualitative method is an appropriate approach to explore the subject's experience and context in depth. This study aims to explore the history, understanding, purpose, benefits, techniques, and effectiveness of marriage counseling. The history of the use of this technique shows the evolution and adaptation of counseling practices, while a precise definition is needed for in-depth understanding. The changing objectives of marriage counseling with social and cultural changes also need to be explored, along with the benefits derived and specific techniques used in its implementation. Evaluation of the effectiveness of marital counseling is important to assess the success of this intervention in resolving marital problems and strengthening the bond between spouses. This research aims to provide a more comprehensive understanding of the practice of marital counseling as well as its relevance in the current societal context.